Legal Analysis of the Implementation of the Rights of Royal Residents of Apartments in Makassar City - Suwandari, Mufitha; Pattenreng, A. Muh. Arfah; Hamid, Abd. Haris (Postgraduate Bosowa University Publishing, 2018)
This research aimed at finding out the implementation of the rights of royal residents and the constraints faced by the residents to obtain their rights. This study was conducted in Royal Apartment in Makassar and Government building office, Makassar. The quantitative method was applied to investigate the implementation of the rights of Royal Residents as well as the constraints faced by the residents to obtain their rights. The results showed that the rights of Royal Residents are implemented well although undeniably some other rights of the Royal residents are not well-implemented. Moreover, the certain rules which regulate the apartment, no socialization regarding the residents’ rights, and no the Association of unit owners and occupants of flats (Perhimpunan Pemilik dan Penghuni Satuan Rumah Susun) become the constraints of Royal Residents, Makassar.